CORRELATION AND PATH COEFFICIENT ANALYSIS OF SHOOT, ROOT MORPHOLOGICAL TRAITS AND MICRONUTRIENT (FE AND ZN) CONTENT ON GRAIN YIELD IN RICE (ORYZA SATIVA L.) UNDER CONTRASTING MOISTURE REGIMES - M. R. SUMA; K. MANJUNATH; H. E. SHASHIDHAR (The Bioscan, 2014)
The relevance of several shoot and root morphological traits in improving grain yield of rice under flooded and aerobic condition were studied. Grain yield was significantly correlated with maximum root length (0.280), root volume (0.323), root dry weight (0.283) and root number (0.319) under aerobic condition. Above ground traits like plant height (0.218), panicle length (0.408), number of productive tillers (0.586) and straw yield per plant (0.433) were showed significant positive correlation with grain yield per plant. Path analysis indicated that root traits like maximum root length (0.897), root dry weight (0.686) and root number (0.639) positive direct effect on grain yield. Above ground traits like plant height (0.648), panicle length (0.993), number of productive tillers (0.895), test weight (0.708) and straw yield per plant (0.236) had direct positive effects on grain yield. These results indicate the role of root traits for improving yield under aerobic situations possibly through improved water and nutrient uptake and also well developed root system will help the plant in maintaining high plant water status which ultimately leads to increase in yield potential under aerobic condition with sufficient amount of Fe and Zn content.